2015
DOI: 10.1007/978-3-319-15248-6_44
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis of Cables with Attached Tuned-Inerter-Dampers

Abstract: Cables are widely used structural elements capable of bearing tensile forces and experience vibration problems due to their slenderness and low mass. In the field of civil engineering, they are mostly used in bridges where the vibrations are mainly induced by wind, rain, traffic and earthquakes. This paper proposes the use of a tuned-inerter-damper (TID) system, mounted on cables to suppress unwanted vibrations. These are to be attached transversally to the cable, in the vicinity of the support, connected betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…TID has been attracting considerable interest because it has great vibration control performance with small mass and compact configuration. A number of literatures [12][13][14][15] have investigated the efficiency of TID for vibration control of cables. Hu et al 16,17 investigated the optimal design and evaluated the performances of various inerter-based dynamic vibration absorbers and isolators including the TID and TVMD.…”
Section: Introductionmentioning
confidence: 99%
“…TID has been attracting considerable interest because it has great vibration control performance with small mass and compact configuration. A number of literatures [12][13][14][15] have investigated the efficiency of TID for vibration control of cables. Hu et al 16,17 investigated the optimal design and evaluated the performances of various inerter-based dynamic vibration absorbers and isolators including the TID and TVMD.…”
Section: Introductionmentioning
confidence: 99%
“…Then Chen et al 30 introduced the TID to the car suspension system, in which the performance of suspension system and ride comfort were effectively improved and the dynamic load to the tire was reduced. In addition, the TID can also be used to control cable vibration 31,32 . However, these vibration absorbers need precise tuning, which is difficult to realize in practice.…”
Section: Introductionmentioning
confidence: 99%
“…By using mechanical amplification mechanisms (such as ball screws, gears, and lever pendulums), inertial devices can provide a larger apparent mass, and inertial force is gradually used for structural vibration control. Lazar et al [26][27][28] replaced the mass part of a tuned mass damper with an inertial mass and constructed a tuned inertial damper (TID). Vibration control analysis of the cable's first vibration mode showed that the TID makes the cable obtain a higher mode damping ratio than the traditional viscous damper.…”
Section: Introductionmentioning
confidence: 99%